Media Online Dalam Melaksanakan Bimbingan Pra Nikah Era New Normal: Online Media in Implementing Pre-Marriage Guidance in the New Normal Era - M. Djakfar Hasbi; Teuku Amnar Saputra (UIN Kiai Haji Achmad Siddiq Jember, 2023)
The Covid-19 pandemic has changed all forms of human activities into new habits. The use of information technology is the basis in every activity carried out. The Office of Religious Affairs (KUA) in implementing Pre-Marriage guidance must also have an innovation in conducting guidance while maintaining health protocols. The purpose of this study was to determine the urgency of online media in carrying out premarital guidance and how the premarital guidance system is implemented using online media at the Office of Religious Affairs (KUA). This study uses a qualitative approach with library research methods. Data analysis was carried out by means of documentation to several reference situations and conditions of the importance of implementing premarital guidance through various related literature. The results of the study show that pre-marital guidance services at the Religious Affairs Office (KUA) are very important given the ongoing pandemic conditions. The use of online media as a service medium is also in line with the direction of human development towards the industrial era 4.0. Online premarital guidance can be done by utilizing several internet-based media such as the use of specially made premarital guidance applications so that the implementation of guidance can be carried out optimally.